AMERICAN VISCERAL LEISHMANIASIS – DISEASE CONTROL STRATEGIES IN DRACENA’S MICROREGION IN ALTA PAULISTA/SP – BRAZIL - D’Andrea, LAZ; Camargo-Neves, VLF; Sampaio, SMP; Kronka, SN; Sartor, IF (Revista do Instituto Adolfo Lutz, 2009)
Despite the adopted measures to control the American Visceral Leishmaniasis (AVL), the disease is spreading in a fast and worrying way throughout west of the State of São Paulo. The aim of this work was to study the variables involved in the disease cycle as well as the effectiveness of the controlling measures. The study was carried out in the micro-region of Dracena, composed of twelve cities, belonging to the Alta Paulista, Far - West of the State of São Paulo. The Superintendence of Control of Endemics and the Institute Adolfo Lutz, Regional Laboratory of Presidente Prudente provided the necessary data. This paper analyzed, from August 2005 to January 2008, the dates of the phlebotomine sand fly detection in the cities and the period in which dogs and human beings were diagnosed, the number of cases of human deaths, prevalence of suspected dogs tested by serology, percentage of euthanasia in suspected dogs, a possible correlation between positive dogs and cases of the disease in humans, and comparing the prevalence among the municipalities of the studied region. It was verified that, despite the strategies adopted in the micro-region of Dracena/SP to control the AVL, the disease continues to grow in worrying way. Some procedures of the AVL Monitoring and Control Program should be reviewed as to their efficacy and others should be supervised, to grant the program greater credibility and effectiveness.